Biochemical and physiological changes associated with estrogenic activity in Xenopus laevis : a model for the detection of endocrine disruption - Hurter, Etienne (Stellenbosch : Stellenbosch University, 2012)
Dissertation (PhD)--University of Stellenbosch, 2003.